Storytelling as an effective method for improving speaking skill in children (2020)
Learning a language is like crawling in early childhood: it has a purpose and there are agents that influence the success of it. One of the important aspects when learning a foreign language is the communication need as human beings, in this case more specifically oral communication. This is precisely one of the problems noticed in a class of English in an extramural English course as foreign language. This being reflected in the oral performance of the students. This research aims to show that when we want to get the knowledge of the processes that influence language acquisition, it is relevant to know that one of them may not be a cognitive issue but factors such as the social milieu in which learning takes place. The input and internal factors play a relevant role in this process, too. The objective is to know why the students present this gap in the oral competence and how, we as researchers can help them improve this ability. To reach these objectives, we implemented instruments that helped us know and follow the learning process of the students and, the implementation of retelling of short stories as a method of improvement of the speaking skill and ability.